Konsep Tasawuf Perspektif Imam Nawawi: Studi Tentang Interpretasi Hadis Sufistik dalam Kitab Al-Arba’in An-Nawawiyyah - suprayitno, muhammad aji; Agus Santoso (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
This research investigates Imam Nawawi's views on Sufism through an analysis of the interpretation of Sufistic hadith contained in his work,